Investigation for one-stop agencies for construction works / Ikhwan Nasir Abdul Manaf - Abdul Manaf, Ikhwan Nasir (1991)
In recent years as the world become more sophisticated, more and more country has been trying to achieve the higher status as an Industrial Country. As in Malaysia this has become a dream for too long and within 30 years of independence, Malaysia has become one of the most developing country in South East Asia as well as in Asia. Lately , construction industries goes up rapidly and it becomes one of the important sector which contribute to Malaysian economy. The Construction sector have been developed with average of 8.1% in 1971 to 1975. In 1973 it 1 goes up to 10.9% and 14% in 1986. Although, it shows the decrease in 1987, it does not mean that the importance of this sector are also decreased. Knowing that construction industry, create a lot of job, the government have looked forward to tackle the problems in construction industry and speed it up again by implementing the North and South Highway and Low Cost Houses Scheme project in 1987. As such the rapid development of the construction industry, has made the existing system obsolete and costly to run in term of time consume. As a result a number of problems still persists within the approval hieracy of the Agencies concerned.